Asian physics olympiad (Ist-8th) : problems and solutions - Yongling, Zheng (London, World Scientific Publishing, 2010)
This book compiles all of the test problems and solutions from the 1st through the 8th Asian Physics Olympiad. Test questions of every paper consist of two parts, a theory section and an experiment section, before which minutes of teams and results of each competition are introduced. It is a rather desirable reference book for both students and teachers of international competition training as well as middle school student contestants.
Appendices 293-308p.
Keywords: Physics